Potential of Activated Platelet-Rich Plasma Against Osteoarthritis: In Vivo Study - Rachmat Hidayat; Patricia Wulandari (Journal of Anesthesiology and Clinical Research, 2022)
Introduction: Osteoarthritis (OA) is a disorder that causes a decrease in the quality of life in elderly patients. The current treatment is only symptomatic in reducing inflammation. This study is one of the exploratory studies to examine the potential of platelet-rich plasma (PRP) in optimizing the improvement of OA patients through the inhibition of inflammatory signals in joint tissue in vivo. Methods: This study is an experimental study with a post-test-only approach with a control group design. A total of 30 rats (Rattus norvegicus) Wistar strain was included in this study and met the inclusion criteria in the form of the male gender, weight between 150-200 grams, and age 8-10 weeks. The rats were divided into 3 groups, namely the group that was not induced by OA and not given PRP (P1), the OA group and given 50 uL saline injection (P2), the OA group and given PRP 50 uL (P3), the treatment was carried out once a week for 4 weeks. Results: The results showed that the P3 group that was treated with platelet-rich plasma showed a significant decrease in interleukin-1ß levels when compared to the P2 group that was induced by OA but was only treated with saline (p<0.05). Conclusion: Platelet-rich plasma has the potential as a biological agent against osteoarthritis in an in vivo study.